NK Cell Subset Redistribution during the Course of Viral Infections - Lugli, Enrico; Marcenaro, Emanuela; Mavilio, Domenico (Frontiers in Immunology, 2014)
Natural killer (NK) cells are important effectors of innate immunity that play a critical role in the control of human viral infections. Indeed, given their capability to directly recognize virally infected cells without the need of specific antigen presentation, NK cells are on the first line of defense against these invading pathogens. By establishing cellular networks with a variety of cell types such as dendritic cells, NK cells can also amplify anti-viral adaptive immune responses. In turn, viruses evolved and developed several mechanisms to evade NK cell-mediated immune activity. It has been reported that certain viral diseases, including human immunodeficiency virus-1 (HIV-1) as well as cytomegalovirus (CMV) infections, are associated with a pathologic redistribution of NK cell subsets in the peripheral blood. In particular, it has been observed the expansion of unconventional CD56neg NK cells, whose effector functions are significantly impaired as compared to that of conventional CD56pos NK cells. In this review, we address the impact of chronic viral infections on the functional and phenotypic perturbations of human NK cell compartment.